Answer:
Perpendicular means that,second gradient equals to first one as:
[tex] - \frac{1}{m} [/tex]
So,conducting the second equation to the form y=mx+c: 3y= -2x-5
[tex]y = - \frac {2}{3}x - \frac{5}{3} [/tex]
So it's gradient is
[tex] - \frac{2}{3} [/tex]
converting to
[tex] - \frac{1}{m} [/tex]
equals to 1.5 or at least
[tex] \frac{3}{2} [/tex]
Y find the equation of the first line you've got to use the formula: y-y1=m (x-x1)
y-1=1.5 (x+6)
y-1=1.5x+9
y=1.5x+10 is the equation of the first line.